Comparative characteristics of healthy newborns cord blood cell composition and G-SCF-mobilized blood from healthy donors - R. Sh. Ibragimov; E. V. Raikina; E. Yu. Osipova; N. N. Zimina; O. A. Maiorova; M. V. Yakovleva; S. A. Roumiantsev (Онкогематология, 2022)
Cord blood cell composition is a short-lasting delivery stress consequence and is similar on adult G-CSF-mobilized peripheral blood.G-CSF realizes biological effect by number of secondary messengers, many of which are also natural effectors of stress. In this research comparative characteristics of cell composition, including lymphocytes subpopulations, CD34+ and CD133+ cells, hematopoietic progenitor cells colony-forming activity and mobilizing cytokines concentration (IL-8, MMP-2, MMP-9), between term newborns cord blood and G-CSF-mobilized peripheral blood is shown.Mobilized cytokines concentration ratio in combination with CD34+ cells count in cord blood and mobilized peripheral blood suggests that delivery stress possibly is not single cause of cord blood features.